Issuing the Challenge: Form, Function and End of Medieval Icelandic Dueling - Hansen, Michael Anthony, 1987- (2016)
This paper offers a re-evaluation of the scholarship surrounding the institution of dueling in medieval Iceland. Primarily this analysis uses the descriptions offered by the family sagas. In this analysis we find that primarily the duel is a method of conflict resolution. The form the duel takes limits the amount of violence that can be performed in the actual duel. In comparison to other means of conflict resolution, the duel offers a faster settlement, with a smaller cost of resources. The overt function of the duel is to illustrate the participants’ willingness to take part in a life-risking contest, and follows the logic that one can contest the legitimate control of resources and women by sheer might. This is contrasted with the practical social use, which is generally to force third party intervention. At the end of the analysis, this paper posits several possible reasons why dueling was outlawed in Iceland, and places it within larger scholarly discussions of medieval Icelandic society. Þessi ritgerð kemur fram með annað viðhorf á einvígum í miðaldrar Íslandi. Í henni eru aðalega notaðar lýsingar sem komu fyrir í Íslenskum miðaldrar sögum. Í þessari ritgerð komust við að því að meginn ástæða einvíga var upplausn ágreininga. Einvígið er byggt upp þannig að það minnkar þann skaðan sem kemur fyrir í alvöru einvíginu. Þegar einvígi er borið saman við aðrar leiðir til að ganga frá ágreininga milli manna er það bæði ódýrast og fjótasta leiðinn. Í einvígi kemur það skýrlega fram að keppendur eru tilbúnir að fórna lífi sínu. Rökin á bakvið það að þeir eru að gera þetta fyrir stjórn yfir auðlindum og kvenmönnum með krafti einum. Það er svo andstætt við það að aðilar nota þetta oft til að blanda þriðja aðila í málið og fá þá til að útkljá vandamálið. Í endanum á ritgerðinni er farið í afhverju einvígi voru svo bönnuð á Íslandi. Síðan er það skoðað samhliða öðrum samræðum um miðaldra Ísland.